(untitled) (Sustainability in Debate, 2016)
SILVA, S. D. e; SÁ, D. M. de; SÁ, M. R. (Org.). Vastos Sertões: história e natureza na ciência e na literatura. Rio de Janeiro: Mauad, 2015. 329 p. ISBN 978.85.7478.796-1.